Leadership or chaos the heart and soul of politics - Schofield, Norman (Springer Berlin Heidelberg, 2011)
Combining elements of economic reasoning and political science has proven to be very useful for understanding the broad variation in economic development around the world. In a sense research in this field goes back to the Scottish Enlightenment and Adam Smith?s original plan in his Theory of Moral Sentiments and Wealth of Nations. Leadership or Chaos by Norman Schofield and Maria Gallego is intended as an advanced, self-contained text in political economy dealing with social choice. The theory and empirical analysis are used to examine democratic institutions and elections in the developed world, and the success or failure of moves to democratization in the less developed world. The book closes with a consideration of current quandaries with regard to political and economic stability and climate change and a discussion of the moral foundations of our society. - Publisher's description.